ANALISIS EFEKTIFITAS MESIN OVERHEAD CRANE DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) DI PT. BTU, DIVISI BOARDING BRIDGE - Asgara, Badik Yuda; Hartono, Gunawarman (Industrial and Systems Engineering Assessment Journal (INASEA), 2014)
The 003/OHC/BRB overhead crane machine is one of the lifting machine for production at PT. Bukaka BRB that has the highest level of breakdown time among other production machines in the company. The purpose of research to determine the effectiveness of the machine overhead crane 003/OHC/BRB, so as to know the appropriate treatment method for the machine. Therefore, it needs to be analyzed from data collected at random to measure the effectiveness of the machine using the Overall Equipment Effectiveness (OEE). OEE calculation is influenced by the availability rate, performance efficiency, and the rate of quality. Overhead Crane machine OEE calculation shows the failure in the ideal value of OEE as a result of the low availability of the machine rate (71.63%) and high breakdown time of the machine. To reduce the rate of breakdown frequency, method of treatment needs to be improved (maintenance). Routine maintenance can be performed by the operator to extend engine life and extending the time of the breakdown, using the method Autonomous Maintenance. The implementation of this method is expected to improve the durability of the engine, so the engine does not often experience breakdown.